2018
DOI: 10.30845/ijbss.v9n5a15
|View full text |Cite
|
Sign up to set email alerts
|

Attitude to Risk of Credit Managers and Efficiency of Credit Management in Real Estate Investment Trusts in Kenya

Abstract: Risk attitude is one of the most important behaviors of managers in any company that affects decisions regarding consumption, saving and investing. Credit management on the other hand, is necessary in real estate organizations to ensure financial stability and business continuity. This study sought to examine the association between attitude to risk of credit managers and the efficiency of credit management in real estate investment trusts operating in Kenya. The study found out that 71.9% of credit managers a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The findings of the study are in line with other earlier studies. In a study by Tchouadep et al (2018) on the risk attitude of credit managers and efficiency of credit management in real estate investment trusts in Kenya found that risk attitude was one of the most important behaviours of managers in any company that influenced their investment decisions. Similarly, in a study on the relationship between risk aversion of individual investors and stock market participation decision among secondary school teachers from Nakuru County, Kenya, Langat and Rop (2019) found out that risk aversion of individual investors also had a significant influence on investment decision among secondary school teachers from the county of Nakuru.…”
Section: Effect Of Risk Attitude On Investment Decisionmentioning
confidence: 99%
“…The findings of the study are in line with other earlier studies. In a study by Tchouadep et al (2018) on the risk attitude of credit managers and efficiency of credit management in real estate investment trusts in Kenya found that risk attitude was one of the most important behaviours of managers in any company that influenced their investment decisions. Similarly, in a study on the relationship between risk aversion of individual investors and stock market participation decision among secondary school teachers from Nakuru County, Kenya, Langat and Rop (2019) found out that risk aversion of individual investors also had a significant influence on investment decision among secondary school teachers from the county of Nakuru.…”
Section: Effect Of Risk Attitude On Investment Decisionmentioning
confidence: 99%